Construction of Indonesian Executive Function Self-Report Scale (IEF-SRS) - Virginia Geraldine Hanny Prasetya; Hery Susanto (Program Studi Psikologi, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Mulawarman, 2024)
Dementia is a cognitive disorder that can affect not only older people but also those who are still young. This condition is called early onset dementia, or EOD, and one of the cognitive functions that is being affected by EOD is executive function. During the period when this research was conducted, Indonesia was still amidst COVID-19 pandemic. This fact is one of the reasons why most people could not leave their homes. This posed a challenge for individuals who wanted to perform an early detection of EOD through cognitive assessments because most of the measurement test for executive function require the tester and the testee to meet face-to-face. Furthermore, there has not been much availability of executive function scales with a self-report format in Indonesia. Based on these phenomena, the researchers decided to develop a measurement test for executive functions for individuals aged 18 and above, to detect EOD. The test consists of 42 items written based on Lezak’s (1982) executive function model. After being tested on 497 participants aged 18-75 years old, the items exhibited high reliability (α=0.841) and strong validity evidence (RSMEA=0.071; GFI=0.99; NFI=0.99; CFI=0.99; IFI=0.99).Demensia merupakan penyakit kognitif yang dapat menyerang tidak hanya lansia, namun juga kaum muda. Penyakit tersebut dinamakan early onset dementia (EOD) dengan salah satu fungsi individu yang dapat terganggu adalah fungsi eksekutif. Pada waktu penelitian ini disusun, Indonesia masih berada pada masa pandemi COVID-19. Hal tersebut menyebabkan banyak orang kesulitan untuk keluar rumah. Hal ini menjadi tantangan bagi individu yang ingin melakukan deteksi dini terhadap EOD karena pada umumnya alat ukur fungsi eksekutif harus dilakukan secara tatap muka. Selain itu, belum banyak alat ukur fungsi eksekutif yang berbentuk self-report. Berangkat dari hal ini, peneliti memutuskan untuk melakukan konstruksi alat ukur fungsi eksekutif untuk individu dari berbagai kalangan usia, sebagai salah satu usaha untuk mendeteksi dini gangguan fungsi kognitif pada individu. Item-item alat ukur ini disusun berdasarkan empat dimensi fungsi eksekutif menurut Lezak (1982;2012). Setelah diujikan pada 497 orang partisipan berusia 18-75 tahun, didapatkan hasil bahwa alat ukur IEF-SRS memiliki reliabilitas (α=0.841) dan bukti validitas (RSMEA=0.071; GFI=0.99; NFI=0.99; CFI=0.99; IFI=0.99) yang baik.